Meningkatkan Aktivitas Belajar Mata Pelajaran Ekonomi Melalui Model Pembelajaran Kooperatif Tipe TPS dan Tipe Jigsaw - Adnyani, Putu Kusuma; Tripalupi, Lulup Endah (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
In the classroom activity the teacher plays a role in the selection of learning models. It will have a great impact on student learning activities. Thus, this research aimed to find out the differences (1) students classroom activity of the experiment group, (2) students classroom activity of the control group, and (3) the significant differences of student classroom activities between the experimental group and the control group. Moreover, the research of study was experimental research. The instruments were using an observation form and documentation and the data were analysing by Independent Sample t-test. The results of this study disclosed (1) the experimental group showed very dynamic, (2) the control group were dynamic and (3) there were significant differences in the learning activities between the experimental group and control group students.